2013
DOI: 10.1371/journal.pntd.0002285
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns of Japanese Encephalitis in China, 2002–2010

Abstract: ObjectiveThe aim of the study is to examine the spatiotemporal pattern of Japanese Encephalitis (JE) in mainland China during 2002–2010. Specific objectives of the study were to quantify the temporal variation in incidence of JE cases, to determine if clustering of JE cases exists, to detect high risk spatiotemporal clusters of JE cases and to provide evidence-based preventive suggestions to relevant stakeholders.MethodsMonthly JE cases at the county level in mainland China during 2002–2010 were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…The most likely spatio-temporal cluster area was located at the southwest of the province, and the high-risk period was from September 2014 to December 2016 (LLR = 2547.64, P < 0.001). The center of this area was in Yushu County, 32.91°N and 96.68°E, which was a circular area with a radius of 261.34 km, covering seven counties: Yushu, Nangqian, Chengduo, Zaduo, Maduo, Qumalai, and Dari. A total of 3916 TB cases were reported in this area during the high-risk period, and the RR was 4.21 (Table 4).…”
Section: Distribution Of Tb Spatio-temporal Clusteringmentioning
confidence: 99%
“…The most likely spatio-temporal cluster area was located at the southwest of the province, and the high-risk period was from September 2014 to December 2016 (LLR = 2547.64, P < 0.001). The center of this area was in Yushu County, 32.91°N and 96.68°E, which was a circular area with a radius of 261.34 km, covering seven counties: Yushu, Nangqian, Chengduo, Zaduo, Maduo, Qumalai, and Dari. A total of 3916 TB cases were reported in this area during the high-risk period, and the RR was 4.21 (Table 4).…”
Section: Distribution Of Tb Spatio-temporal Clusteringmentioning
confidence: 99%
“…All cases are diagnosed according to the China National diagnostic criteria for Japanese encephalitis (Ministry of Health, 2006) that an individual who lived in an epidemic area during the vector-biting season or traveled to an epidemic area within 25 days prior to illness onset, with one of these following laboratory criteria for diagnosis: presence of JEV-specific IgM antibody in a single sample of cerebrospinal fluid or serum by using the enzyme-linked immunosorbent assay (MAC ELISA) with a JEV IgM-capture ELISA kit (Shanghai B&C Biological Technology Co., Ltd., Shanghai, China) as described in published articles (Ye et al, 2010), JE virus antigens, a 4-fold rise in JE virus-specific antibody, JE virus genome in samples by PCR, or isolated JE virus (Wang et al, 2013).…”
Section: Japanese Encephalitis Datamentioning
confidence: 99%
“…The effect of vaccination against vaccine-preventable diseases can only be assessed properly, after controlling for climate variability [44] and nonclimatic confounding factors such as socio-demographic and economic changes in the analytical models [98]. However, this review found that the effect of non-climatic factors has been neglected by most studies; only a few studies included nonclimatic factors.…”
Section: Discussionmentioning
confidence: 99%